NUTRITIONAL AND ENVIRONMENTAL FACTORS DETERMINING DHA STATUS IN PREGNANT AND LACTATING WOMEN: IMPLICATIONS FOR MATERNAL AND NEONATAL HEALTH - Anna Karcz,; Maria Kaniecka,; Barbara Pająk,; Oliwia Wróblewska,; Małgorzata Dworniczak,; Sofiya Salash,; Aleksandra Romaniuk,; Jakub Majewski,; Hubert Bołdys-Żegocki,; Artur Koza, (International Journal of Innovative Technologies in Social Science, 2025)
The intake of omega-3 polyunsaturated fatty acids, particularly docosahexaenoic acid (DHA), is essential for the proper development of the fetus and for maintaining the health and well-being of the pregnant woman, as well as of both the mother and the infant during the lactation period.Numerous studies have demonstrated the beneficial effects of DHA on the development of the nervous system and retinal function, as well as its role in reducing the risk of preeclampsia, preterm delivery, low birth weight, postpartum depression, perinatal maternal mortality, and neonatal intensive care unit admissions. Moreover, DHA has been shown to positively influence the clinical course of certain neonatal disorders after birth.Available data suggest that the dietary and supplemental intake of DHA among pregnant women in Poland may be insufficient compared with current nutritional recommendations. The richest dietary sources of DHA include fatty fish and seafood; however, it is advisable to select species with the lowest levels of methylmercury contamination. Storage and thermal processing affect the omega-3 content in food. Vegetarian women may be particularly susceptible to DHA deficiency. Dietary supplementation with DHA derived from controlled microalgae cultures or fish oils can effectively compensate for inadequate intake.Maintaining an appropriate balance between omega-3 and omega-6 fatty acid consumption is crucial. It is also hypothesized that eicosapentaenoic acid (EPA) may be required for the efficient utilization of DHA by the fetus and may contribute to a reduced risk of preterm birth and preeclampsia. Consumption of DHA increases the risk of macrosomia in the fetus and may influence the extension of pregnancy beyond 42 weeks.